The Role of Anxiety Sensitivity and Emotion Regulation Difficulties in the Relationship Between Sensory Processing Sensitivity and Anxiety - Seçgin, Pelin; Koç, Volkan (Semmelweis University Institute of Mental Health, 2026)
Introduction: Sensory-processing sensitivity (SPS) describes how deeply and intensely individuals process various environmental stimuli. SPS, as an adult temperament trait, may influence different aspects of an individual’s life. Aim: This study explored potential mediating roles of anxiety sensitivity (AS) and emotion regulation difficulties (ERD) in the relationship between SPS and trait anxiety (TA). Methods: Participants (N = 420; 60.5% female; age range: 18–61 years) were administered the Highly Sensitive Person Scale, Trait Anxiety Inventory, Anxiety Sensitivity Index-3, and Difficulties in Emotion Regulation Scale. Results: Results of the stepwise nested regression models indicated that SPS, AS, and ERD significantly predicted trait anxiety, with the final model explaining 54% of the variance. SPS was a significant predictor initially, but its effect became nonsignificant after AS and ERD were included, indicating a full mediation pattern. Serial multiple mediation analysis indicated that the association between SPS and trait anxiety was fully mediated by AS and ERD, with AS demonstrating a significant independent indirect effect, whereas the indirect effect of ERD alone was not statistically significant. The sequential pathway from SPS to AS to ERD to trait anxiety was statistically supported, and gender remained a significant covariate throughout. Conclusions: The findings indicate that the association between SPS and trait anxiety is fully accounted for by AS and ERD rather than by a direct relationship. These results underscore the importance of considering sequential psychological mechanisms and covariate-adjusted models when examining vulnerability to trait anxiety.
Keywords: Anxiety sensitivity; Emotion regulation; Sensory processing sensitivity; Serial mediation; Rrait anxiety